ChemInform Abstract: Na8Lu2(CO3)6F2 and Na3Lu(CO3)2F2: Rare Earth Fluoride Carbonates as Deep‐UV Nonlinear Optical Materials. Issue 41 (19th September 2013) - Luo, Min; Ye, Ning; Zou, Guohong; Lin, Chensheng; Cheng, Wendan
Abstract The two new title compounds (IV) and (V) are characterized by single crystal XRD, UV/VIS diffuse reflectance spectroscopy, second harmonic generation measurements, and DFT computations.